PREVALENCE OF PRE AND POSTPARTUM DEPRESSION SYMPTOMS AND SOME RELATED FACTORS (BABOL 2006-2007) - H Salmalian; F Nasiri Amiri; F Khirkhah (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul, 2008)
BACKGROUND AND OBJECTIVE: Postpartum depression endangers mothers health and has negative effect on her social communication and infant development. Depression symptoms in %50 of women who experience postpartum depression are seen during pregnancy time. The aim of this study was to detect depression symptoms and its effective factors during pregnancy and prevention of familial and individual problems caused by postpartum depression.METHODS: This cross-sectional study was performed on 263 pregnant women referred to health centers of Babol, Iran. All women completed a questionnaire consists of demographic information, obstetrics and standard Beck-test in the last three months of pregnancy and 4-8 weeks after delivery. Rate of depression based on scale divided into three groups: non depression, mild depression and moderate depression. Data was analyzed by Wilcoxon statistical test and Linear Regression. FINDINGS: Mean score of depression symptoms before delivery was 18.7±6.4 and after delivery was 20.4±7.5 that showed no significant difference. There was a significant relationship between age, husband’s job and education, gravidity, family income, worry about delivery expense, history of abortion, reaction to pregnancy, present pregnancy complications, last pregnancy outcome, and education regarding delivery in prenatal care with pre and postpartum depression (p=0.001). There was a significant difference between type of delivery, postpartum complication and inconsistency between infant and mother’s benefit with postpartum depression (p=0.001). But there was no significant relationship between woman’s job and living place with pre and postpartum depression. CONCLUSION: According to the results of this study, pregnancy is a proper time for screening mothers for postpartum depression. Considering negative effect of this disorder on family, more attention should be given to its related factors.